Interference during the post-KR interval can enhance learning motor skills - Magill, R.; Lee, T. D. (Paper presented at the Annual Conference of the Canadian Society of Psychomotor Learning and Sport Psychology, Kingston, ON., 1984)
Implication of the study: For effective learning to occur between repetitions of learning trials there has to be a minimum amount of time to allow feedback from a trial to produce a learning effect. That effect does not seem to be modified to any great extent if between-trials activity is related or unrelated to what is being learned. This means that it is possible to repeat trials too close together. Such rapidity does not allow the full learning effects from each repetition to occur.